Pemilihan Squad di Game E Football Mobile Menggunakan Metode Topsis - Pratama, Ilham; Wulan, Nur (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
In the 2024 mobile e-football game, gamers are challenged to build a strong team (squad) by selecting quality players. Most gamers rely on intuition or previous gaming experience in building their squad, which is often not optimal. The main obstacle in selecting the best squad is the number of variables and data that must be considered. Player statistics play an important role in determining a player's effectiveness on the field. The purpose of this research is to create a decision support system to use to form the best squad (team) in the 2024 mobile e-football game to assist gamers in determining players withmore systematic and data-based information to be included in the squad. This study uses the TOPSIS method which is one of the multi-criteria decision-making techniques used to select the best alternative from a set of existing alternatives. The results of the study show that the decision support system of the TOPSIS method can be used as an option to choose players in the 2024 mobile e-football game. From the results and testing of this decision support system, the players were allowed to be included in the squad based on the data input into the system, namely, the position of goalkeeper M. ter Stegen. Defender D. Alaba; Marquinhos; J. Kounde; and Eder Milirao. Midfielder J. Kimmich; J. Bellingham; and J. Musiala. Attacking player K. Benzema; H. Kane; and K. Mbappe.